2009
DOI: 10.3121/cmr.2009.824
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Inhaled Corticosteroid on Glucose Control in Type 2 Diabetes

Abstract: Objective:To determine the effect of inhaled corticosteroid (ICS) therapy on glucose control in adults with type 2 diabetes mellitus and coexisting asthma or chronic obstructive pulmonary disease (COPD).Design: A prospective randomized, double-blind, double-dummy placebo-controlled, crossover investigation of inhaled steroids and oral leukotriene blockers. Setting:A United States Department of Veterans Affairs Health Care System outpatient setting.Participants: Adults with type 2 diabetes and asthma or COPD.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 26 publications
4
34
0
Order By: Relevance
“…73.91% patients were on systemic corticosteroid therapy which is higher in comparison to current trends in developed countries as shown in previous studies by Miravitlles M et al and Jackevicius C at al. 10,11 In this study only 26.09% patients were taking inhaled corticosteroids and which is quite lower than studies conducted in developed [12][13][14][15] In current study 15.22% patients had diabetes mellitus which is comparable to studies conducted by Slatore CG et al, Faul JL et al, Suissa S et al and Gartlehner G et al [27][28][29][30] Impaired glucose tolerance was found in 30.43% patients. Smyllie HC et al and Slatore CG et al concluded that glucose control is more difficult with steroid based therapy in COPD.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…73.91% patients were on systemic corticosteroid therapy which is higher in comparison to current trends in developed countries as shown in previous studies by Miravitlles M et al and Jackevicius C at al. 10,11 In this study only 26.09% patients were taking inhaled corticosteroids and which is quite lower than studies conducted in developed [12][13][14][15] In current study 15.22% patients had diabetes mellitus which is comparable to studies conducted by Slatore CG et al, Faul JL et al, Suissa S et al and Gartlehner G et al [27][28][29][30] Impaired glucose tolerance was found in 30.43% patients. Smyllie HC et al and Slatore CG et al concluded that glucose control is more difficult with steroid based therapy in COPD.…”
Section: Discussionsupporting
confidence: 61%
“…[25][26][27] One study shows 15% of COPD patient requires additional treatment for hyperglycemia as compared to 4% of control group. [28][29][30] In addition to this some case reports describe loss of glucose control in patient receiving ICS based therapy. 13,31,32 On the other hand, lung health study-2 did not demonstrate an increased risk for a new diagnosis of diabetes mellitus in individual receiving ICS based therapy.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study 69 performed in a large Veterans Affairs population suggested that, although ICSs were not associated with hyperglycemia in individuals without DM, among people with DM, ICS use was correlated with glucose levels in a dose-dependent manner. A number of small studies of adults 73,74 have similarly linked hyperglycemia among diabetic individuals, but not individuals without DM, to ICS use.…”
Section: Primary Recommendationsmentioning
confidence: 99%
“…Faul et al 32 did not find a significant impact of corticosteroid use on changes in HbA1c levels, despite suggesting careful monitoring of blood glucose levels for patients initiating use of corticosteroids. It seems sensible that, although starting corticosteroids or a change in dosage can lead to short periods of increased glycaemia, chronic corticosteroid use is easily controlled by adapting the treatment prescription.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%